PPP Mean Reversion Estimation for Iceland. A Unit-Root & Single-Equation Cointegration Approach Using New Long-Run Time-Series - Páll Þórarinn Björnsson 1982- (2014)
This study examines empirical evidence regarding long-run relative purchasing power parity (PPP) convergence for Iceland. The aim is to examine whether the Icelandic króna’s fluctuating exchange rate exhibits a tendency towards mean-reversion; that is, to determine if an equilibrium real exchange rate exists for the ISK. Long-run trade-weighted nominal and real effective exchange rate indices are constructed, spanning a 117-year period of the ISK’s history. Annual and monthly data are used to construct the indices. The historical exchange rates are calculated as geometrically weighted chain indices with current trade weights based on Iceland’s foreign trade in goods. The consumer price index (CPI) is used for deflation. Data are based on 13 to 15 of Iceland’s largest trading partners, which accounted for at least 64 per cent of Iceland’s total foreign trade in goods each year, during the period in question. Empirical estimations are applied to the new time-series. Unit-root and single-equation cointegration tests are performed for stationarity estimation. Mean-reversion from PPP deviation is analysed via autoregressive models, with half-life calculations based on ordinary least squares (OLS) parameter estimates. Empirical estimations are applied to the period as a whole, as well as individual estimations for two sub-periods, due to a structural break in the series. Separate estimations are also carried out for post-1988 period, using monthly data. The results are consistent with results from similar studies on purchasing power parity. Evidence supporting relative PPP convergence is found for all but one of the periods, (post-1988), where results from unit-root and cointegration tests contradict, indicating failure of PPP convergence for the period. Half-life estimates, are around four years for the period as a whole. The most rapid mean reversion appears during the inter-war and post-1981 periods. The inter-war period also shows the least volatility in the real exchange rate of the ISK. Keywords: International ...